RANCANG BANGUN SISTEM PENDETEKSI ASAP KEBAKARAN MENGGUNAKAN NODEMCU ESP8266 BERBASIS INTERNET OF THINGS (STUDI KASUS : SMK IPTEK TANGSEL) - Dila Oktiviani; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2024)
This research aims to design a tool to become a fire detection system in a school. Currently fire detection is still done manually based on human senses, which has many drawbacks, including delays in school occupants knowing and responding to fire and smoke at school. To overcome the problem above, namely, by making a fire detector. This fire detection system uses NodeMCU as a microcontroller and two sensors, namely a fire sensor and a smoke sensor, as fire and smoke detection devices. NodeMCU is connected to fire sensors and smoke sensors installed in schools. When the fire sensor or smoke sensor detects signs of fire, NodeMCU will give a signal to the alarm system connected to the user's smartphone to warn residents or school officials. This system is very useful for reducing the risk of fire occurring in schools and helping residents or school officials to immediately take appropriate action when a fire occurs. Based on the design, development, implementation of the prototype and the research that has been carried out, it can be concluded that the final conclusion from the design of a fire detection device is that the system can work properly and carry out its function as a good detector of fire and smoke, which makes residents and school staff aware of the presence of fire. fire and smoke in the school environment earlier, also provide notifications to the smartphones of residents and school staff if fire or smoke is detected by the sensor